2013
DOI: 10.1371/journal.pone.0085231
|View full text |Cite
|
Sign up to set email alerts
|

Abl Family Kinases Regulate Endothelial Barrier Function In Vitro and in Mice

Abstract: The maintenance of endothelial barrier function is essential for normal physiology, and increased vascular permeability is a feature of a wide variety of pathological conditions, leading to complications including edema and tissue damage. Use of the pharmacological inhibitor imatinib, which targets the Abl family of non-receptor tyrosine kinases (Abl and Arg), as well as other tyrosine kinases including the platelet-derived growth factor receptor (PDGFR), Kit, colony stimulating factor 1 receptor (CSF1R), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 70 publications
(106 reference statements)
6
89
1
1
Order By: Relevance
“…Recent studies have identified roles for members of the ABL family of non-receptor tyrosine kinases (ABL1 and ARG) and RhoA and ROCK in histamine-induced VE leakage; therefore, we examined histamine and IL-4C induction of ABL1 kinase activity 15, 52 . Employing the immortalized human endothelial cell line (EA.hy926), we firstly examined ABL1 kinase activity after histamine and IL-4C stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have identified roles for members of the ABL family of non-receptor tyrosine kinases (ABL1 and ARG) and RhoA and ROCK in histamine-induced VE leakage; therefore, we examined histamine and IL-4C induction of ABL1 kinase activity 15, 52 . Employing the immortalized human endothelial cell line (EA.hy926), we firstly examined ABL1 kinase activity after histamine and IL-4C stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested differential roles for the Abl family kinases, c-Abl and Arg, in mediating EC barrier function (2,11). Because imatinib inhibits both these kinases, siRNA technology was employed to individually downregulate the expression of c-Abl or Arg in HPAEC to investigate the specific functions of c-Abl and Arg in our models of EC dysfunction.…”
Section: Roles Of C-abl and Arg In Mediating Endothelial Dysfunctionmentioning
confidence: 99%
“…Some clinical trials showed an association of Imatinib treatment with resolution of edema (59)(60) (61). Preclinical trials demonstrated that Imatinib reduces edema via preservation of endothelial barrier integrity (62) (63). Inhibition of Abl kinase activity causes an activation of Rac1 and Rap1 and thereby a stabilization of endothelial barrier, as mentioned before.…”
Section: Rac1 Represents a Central Key Player In The Regulation Of Vamentioning
confidence: 93%